Leasing insights for Elite Hotels - Husain, Abdul Rashid; Abdullah, Azrul (Faculty of Accountancy, 2025)
The integration of high-technology equipment in the hospitality industry has become essential for operational efficiency and enhanced guest experience (Buhalis, 2008). Elite hotels is premier luxury resort in Malaysia, utilizes a wide array of technological tools, including laptops, desktop computers, printers, fax machines, telecommunication systems, and multifunction copiers (photostat machines) (Kasavana & Cahill, 2003; Ivanov & Webster, 2017). This article aims to evaluate which of these equipment types should be leased from third-party vendors in accordance with Malaysian Financial Reporting Standard 16 (MFRS 16) Leases. The analysis provides strategic recommendations, financial implications, and considerations for optimizing cost management and ensuring compliance with current accounting standards.